1999
DOI: 10.1097/00000542-199902000-00012
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Fentanyl on Sevoflurane Requirements for Somatic and Sympathetic Responses to Surgical Incision 

Abstract: MAC and MAC-BAR decreased similarly with increasing concentrations of fentanyl in plasma, showing an initial steep reduction followed by a ceiling effect. In the presence of N2O, MAC and MAC-BAR decreased similarly but did not exhibit a ceiling effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
52
5
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(66 citation statements)
references
References 23 publications
6
52
5
3
Order By: Relevance
“…18 In contrast to somatic reflexes however, hemodynamic responses to noxious stimuli do not correlate well with end-tidal drug concentration. 19 It is for the above reasons that the effects of remifentanil on MAC of sevoflurane and not MAC-BAR of sevoflurane were studied.…”
Section: Discussionmentioning
confidence: 95%
“…18 In contrast to somatic reflexes however, hemodynamic responses to noxious stimuli do not correlate well with end-tidal drug concentration. 19 It is for the above reasons that the effects of remifentanil on MAC of sevoflurane and not MAC-BAR of sevoflurane were studied.…”
Section: Discussionmentioning
confidence: 95%
“…A composition of gender in dogs is a great difference in experimental protocol between the present study (all intact female dogs) and the study reported by Love et al [14] (all intact male dogs). Gender difference in the MAC-BAR was supposed in human patients [11,24]. Further investigation is necessary to confirm the effect of gender on the MAC-BAR in dogs.…”
mentioning
confidence: 95%
“…The value of ratio of MAC-BAR/MAC is quite disparate between volatile anesthetic agents and species. It is reported that the ratio of MAC-BAR/MAC was 2.24 MAC for sevoflurane in human [11], 2.64 MAC for isoflurane in goats [1], 1.11 MAC for isoflurane in cats [15] and 1.48 MAC for halothane in cats [21]. Differences in study design, species, age, and volatile anesthetic agents may account for variability in MAC-BAR and MAC results.…”
mentioning
confidence: 99%
“…32,33 The concept of general balanced anesthesia is defined by the co-administration of several pharmacological agents, so as to enhance their beneficial effects while reducing the side effects of individual drugs administered in high doses. 34 Clinical studies have reported that the reduction of intraoperative opioid doses is associated with diminished postoperative pain and reduced morphine consumption. 10,11 In the present study, repeated fentanyl administrations every 15 min (4 9 60 lg kg -1 ) on D 0 induced an early (lasting 4 h) and delayed and long-lasting hyperalgesia (lasting 3 days).…”
Section: Discussionmentioning
confidence: 99%